Embriologi dalam Al-Qur’an: Kajian Tafsir Ilmi terhadap QS. Al-Mu’minun: 12-14 dan Temuan Sains Modern: Penelitian - Andi Rosa; Anisah Jahroh; Naesyah Fazriah; Suci Purnama Sari; Diyah Nuralifah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This research aims to examine the verses of the Qur'an about the process of human creation, especially QS. Al-Mu'minun verses 12–14, through the approach of scientific interpretation and comparing it with the findings of modern embryology. These verses gradually describe the process of human occurrence starting from the essence of the earth, nuthfah (semen), 'alaqah (a clot of blood), to mudhghah (a lump of flesh), which is then formed into bones and wrapped in meat. This study uses a qualitative-descriptive method by examining classical and contemporary interpretations, as well as scientific data from modern embryology. The results of the study show that there is an alignment between the description of the Qur'an and the development of modern science, especially in the stages of fetal development. This shows that the Qur'an is not only a book of spiritual guidance, but also contains scientific cues that are relevant to scientific findings. Nevertheless, the scientific interpretation of the verse must still be done carefully so as not to get caught up in the imposition of meaning (scientific fallacy).